International wrestling performance - tendencies in the pre-Olympic year - Tünnemann, H.
1 Analyses of the World Championships 1995 in Atlanta and Prague 1.1 Analyses of wrestling strategies 1.2 Particular features of certain countries and wrestlers 2. Analysis of wrestling performance in the age-group juniors 2.1 Specific features of certain countries and wrestlers 2. 2 Analysis of wrestling technique 3 Recommendations for the training